A missense mutation in Ehd1 associated with defective spermatogenesis and male infertility - Meindl, Katrin; Issler, Naomi; Afonso, Sara; Cebrian-Serrano, Alberto; Müller, Karin; Sterner, Christina; Othmen, Helga; Tegtmeier, Ines; Witzgall, Ralph; Klootwijk, Enriko; Davies, Benjamin; Kleta, Robert; et al. (Frontiers in Cell and Developmental Biology, 2023)
Normal function of the C-terminal Eps15 homology domain-containing protein 1 (EHD1) has previously been associated with endocytic vesicle trafficking, shaping of intracellular membranes, and ciliogenesis. We recently identified an autosomal recessive missense mutation c.1192C>T (p.R398W) of EHD1 in patients who had low molecular weight proteinuria (0.7-2.1 g/d) and highfrequency hearing loss. It was already known from Ehd1 knockout mice that inactivation of Ehd1 can lead to male infertility. However, the exact role of the EHD1 protein and its p.R398W mutant during spermatogenesis remained still unclear. Here, we report the testicular phenotype of a knockin mouse model carrying the p.R398W mutation in the EHD1 protein. Male homozygous knockin mice were infertile, whereas the mutation had no effect on female fertility. Testes and epididymes were significantly reduced in size and weight. The testicular epithelium appeared profoundly damaged and had a disorganized architecture. The composition of developing cell types was altered. Malformed acrosomes covered underdeveloped and misshaped sperm heads. In the sperm tail, midpieces were largely missing indicating disturbed assembly of the sperm tail. Defective structures, i.e. nuclei, acrosomes, and sperm tail midpieces, were observed in large vacuoles scattered throughout the epithelium. Interestingly, cilia formation itself did not appear to be affected, as the axoneme and other parts of the sperm tails except the midpieces appeared to be intact. In wildtype mice, EHD1 colocalized with acrosomal granules on round spermatids, suggesting a role of the EHD1 protein during acrosomal development. Wildtype EHD1 also co-localized with the VPS35 component of the retromer complex, whereas the p.R398W mutant did not. The testicular pathologies appeared very early during the first spermatogenic wave in young mice (starting at 14 dpp) and tubular destruction worsened with age. Taken together, EHD1 plays an important and probably multifaceted role in spermatogenesis in mice. Therefore, EHD1 may also be a hitherto underestimated infertility gene in humans.